S = r = 1 ∑ ∞ [ 2 r 1 ⋅ r ( r + 1 ) ( r + 1 ) 2 + 1 ]
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is a simple summation of rth term 2^(-1) { 1 + (2/r) - (1/(r + 1))} , giving 2 sum as plus minus terms cancel in next term. Check by putting values for r.
S = ∑ i = 1 ∞ 2 i 1 + ∑ j = 1 ∞ j 2 j − 1 1 − ( j + 1 ) 2 j 1 = 1 + 1 = 2 Note the second summation is converging as it is of the form f(k)-f(k+1)
Problem Loading...
Note Loading...
Set Loading...
T n = 2 r 1 . r ( r + 1 ) ( r + 1 ) 2 + 1
= 2 r 1 . r ( r + 1 ) ( r + 1 ) 2 − 1 + 2
= 2 r 1 ( r ( r + 1 ) r ( r + 2 ) + r ( r + 1 ) 2 )
= 2 r 1 ( ( r + 1 ) r + r + 1 2 + r 2 − r + 1 2 )
= 2 r 1 ( ( r + 1 ) r + 1 − 1 + r + 1 2 + r 2 − r + 1 2 )
= 2 r 1 ( 1 − ( r + 1 ) 1 + r + 1 2 + r 2 − r + 1 2 )
= 2 r 1 + 2 r 1 ( r 2 − r + 1 1 )
adding all
we get
= 2 1 1 2 + 2 1 ( 1 2 − 2 1 ) + 2 2 1 ( 2 2 − 3 1 ) + 2 3 1 ( 3 2 − 4 1 ) + . . . . . . . . . . . . . . . . . . . . . . . . . . .
1 + 1 − 2 . 2 1 + 2 . 2 1 . . . . . . . . . . . . . . . . . . . . . .
= 2
OR Simply open the square in the numerator and do the above you will get the answer